Disorder induced interface states and their influence on the AI/Ge nanowires Schottky devices - Simon, R. A.; Kamimura, H.; Berengue, O. M. [UNESP]; Leite, E. R.; Chiquito, A. J. (American Institute of Physics (AIP), 2013)
It has been demonstrated that the presence of oxide monolayers in semiconductor surfaces alters the electronic potential at surfaces and, consequently, can drastically affect the electronic transport features of a practical device such as a field effect transistor. In this work experimental and theoretical approaches to characterize Al/germanium nanowire Schottky devices by using samples covered with a thin oxide layer (2nm width) were explored. It was also demonstrated that the oxide layer on Ge causes a weak dependence of the metal work function on Schottky barrier heights indicating the presence of Fermi level pinning. From theoretical calculations the pinning factor S was estimated to range between 0.52 and 0.89, indicating a weak Fermi level pinning which is induced by the presence of charge localization at all nanowires' surface coming from interface states. (C) 2013 AIP Publishing LLC.